(untitled) (Sains Humanika, 2021)
The decline in the percentage of students into science streams and subsequently taking physics subjects is a critical issue in the country. This study aims to identify the level of interest, attitude, and perception of Form 3 students in learning Physics and the influence of these variables on the post Form 3 stream enrolment selection. A total of 112 students in the district of Johor Bahru responded to a set of questionnaires on students’ interests, attitudes, and perceptions towards physics. The validity and reliability of the instrument were analyzed using Rasch model analysis. Descriptive and inferential statistical analyses were computed using Statistical Package for Social Science (SPSS) version 15.0 software to determine the means, standard deviations and t-test results. Results show that the level of students’ interest in Physics is moderate (mean = 3.52, SD = 0.64), while the level of students’ attitudes toward Physics is high (mean = 3.89, SD = 0.67) and the students’ perceptions on the teaching and learning of Physics is also high (mean = 3.80, SD = 0.60). There are significant differences between the stream selection with interest, attitude, and perception on Physics (interest (t=5.135), attitude (t=4.798) and perception (t=3.664)). Therefore, the research findings show that these variables influence the Form 3 students’ stream selection in Form 4. This shows that students’ involvement in science and physics can reach a 60:40 ratio for science to non-science, with higher interest, positive attitudes and perceptions towards physics.